1997
DOI: 10.1002/(sici)1097-0185(199701)247:1<9::aid-ar2>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and functional analyses of nephropathy in calmodulin-induced diabetic transgenic mice

Abstract: Background Previous animal models of diabetic nephropathy have used diabetic animals for which the underlying defect was either uncertain or the diabetes was induced by potentially specific toxins. In this report, we describe the renal abnormalities in a transgenic mouse model that develops early‐onset diabetes due to overexpression of calmodulin in pancreatic beta cells. Methods Renal tissues were collected from normal and transgenic mice at 112, 182, and 300 days. These were prepared for light microscopic ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…The OVE26 transgenic diabetic mouse is particularly interesting because, despite substantial pancreatic β‐cell–specific damage (Epstein et al,1989,1992) and blood glucose levels frequently exceeding 600 mg/dl (Zheng et al,2004), insulin secretion is sufficient to allow these mice to live as long as 450 days without treatment. Significantly, these mice show numerous morphological features that parallel chronic complications of DN in humans (Carlson et al,1997,2003; Zheng et al,2004). Moreover, they are prone to early and frequently severe microalbuminuria and the major blood pressure effect is hypertension (Zheng et al,2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The OVE26 transgenic diabetic mouse is particularly interesting because, despite substantial pancreatic β‐cell–specific damage (Epstein et al,1989,1992) and blood glucose levels frequently exceeding 600 mg/dl (Zheng et al,2004), insulin secretion is sufficient to allow these mice to live as long as 450 days without treatment. Significantly, these mice show numerous morphological features that parallel chronic complications of DN in humans (Carlson et al,1997,2003; Zheng et al,2004). Moreover, they are prone to early and frequently severe microalbuminuria and the major blood pressure effect is hypertension (Zheng et al,2004).…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics include significant nephropathic features, which have been well characterized. As examples, OVE26 kidney weights were almost doubled between 2 and 5 months (Zheng et al,2004), and morphometric analyses have shown an increase in GBM thickness (Carlson et al,1997;2003), glomerular volume, and mesangial matrix area (Zheng et al,2004). Interestingly, significant albuminuria was frequently seen by 2 months of age, and urinary albumin excretion (UAE) rates increased progressively with age (Zheng et al,2004).…”
mentioning
confidence: 99%
“…For electron microscopy photomicrographs, kidney cortex was prepared and analyzed as we and others have previously described (7,8,2024). …”
Section: Methodsmentioning
confidence: 99%
“…The most likely cause of too much proximal tubule cell uptake is very high concentrations of albumin in the tubule lumen from leaking glomeruli. We previously described structural abnormalities in the OVE glomerular filtration barrier [12, 13, 2125] and functional results showing that a subset of OVE glomeruli have severe leakage of albumin [15]. Supplemental Figure 3 shows that OVE glomeruli still filter TR-albumin, despite possessing obviously abnormal podocyte organization, as revealed by a podocyte GFP transgene [26].…”
Section: Discussionmentioning
confidence: 99%